Robert E. Lee, young Confederate - Monsell, Helen Albee, 1895-; Arthur, James; Morrow, Gray (New York : Aladdin Books ; London : Collier Macmillan Publishers, 1986)
A biography focusing on the childhood of the man who turned down the field command of the United States Army and became the leader of the Confederate Army during the Civil War.
Reprint. of the ed. : Indianapolis : Bobbs-Merrill, 1983, c1960. (Childhood of famous Americans series)
Published 1937 under title: Boy of old Virginia, Robert E. Lee.
4.0
3-6
Keywords: Lee, Robert E. -- 1807-1870 -- Childhood and youth -- Juvenile literature; Lee, Robert E. -- 1807-1870.; Lee, Robert E., -- 1807-1870.; Confederate States of America. -- Army -- Biography -- Juvenile literature; Generals -- United States -- Biography -- Juvenile literature; Generals; Generals -- Biography